1976
DOI: 10.2466/pr0.1976.38.3.915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mnemonic Encoding Techniques on Immediate and Delayed Serial Learning

Abstract: 60 undergraduates participated in a serial learning task comparing three instructional strategies: the story and pegword mnemonic techniques (which both stress order relationships between test items) and an uninstructed control group using subject-determined, idiosyncratic study and rehearsal methods. All subjects learned four 10-item lists followed by an immediate recall after each list presentation and a delayed recall after completion of all four lists. Results showed no significant differences between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Also, Bower and Winzenz (1970), using concrete word pairs, found that imagery led to better recall performance than ready-made or self-produced sentences, and better recognition performance than ready-made sentences. The only inconsistent finding is by Borges, Arnold and McClure (1976), who used concrete materials, and found the sentence mnemonic led to better performance than imagery. However, unlike the other studies, Borges et al compared the sentence mnemonic to the imagery peg-word system, and so the results may not reflect the comparative value of imagery and sentence mnemonics per se.…”
Section: Effectiveness In Comparison To Other Memory-aiding Strategiesmentioning
confidence: 99%
“…Also, Bower and Winzenz (1970), using concrete word pairs, found that imagery led to better recall performance than ready-made or self-produced sentences, and better recognition performance than ready-made sentences. The only inconsistent finding is by Borges, Arnold and McClure (1976), who used concrete materials, and found the sentence mnemonic led to better performance than imagery. However, unlike the other studies, Borges et al compared the sentence mnemonic to the imagery peg-word system, and so the results may not reflect the comparative value of imagery and sentence mnemonics per se.…”
Section: Effectiveness In Comparison To Other Memory-aiding Strategiesmentioning
confidence: 99%
“…Some studies report no differences in retention comparing a mnemonic condition with a rote-rehearsal condition using retention intervals up to 8 weeks [15,16] . By contrast, other studies document forgetting fi ndings in favor of tutor-provided mnemonic strategies compared to control conditions [17][18][19][20] , although the bulk of research suggests that non-mnemonic self-initiated strategies might be more effective than tutor-provided instructions for long-term retention [21][22][23][24][25] . However, in these studies the different mnemonics or strategies were provided to the subjects during the encoding phase of the testing situation and were thus used with little or no practice.…”
mentioning
confidence: 61%
“…Similarly, Santa, Fuskin, and Yio (1973) found a story technique (linking) to be superior to a pegword technique with respect to the final recall of six lists of ten words each. With respect to serial learning, Borges, Arnold, and McClure (1976) found a story mnemotechnic superior to a pegword mnemotechnic for the delayed recall of four lists of ten items each. It would appear, then, that unless it is desirable to recall rapidly by list position, that a linking story mnemotechnic should be preferred for list learning.…”
Section: Relative Effectiveness Of Mnemotechnics For List Learningmentioning
confidence: 99%